Exploring the Role of Accounting Practices and Financial Analysis: A Case Study in Perfect Zone Buraidah - Maspul, Kurniawan Arif; Akrem, Ahmed Mohammed (CV.RIZANIA MEDIA PRATAMA, 2024)
This compelling case study delves into the critical role of accounting techniques and financial analysis in business management. The study explores the obstacles faced and the tactics used to overcome them by drawing on the firsthand experiences of an accountant at a startup business. The study emphasizes the importance of precise inventory management, budgeting and forecasting, financial monitoring, and sales performance analysis in attaining long-term growth and profitability. The findings emphasize the significance of combining accounting theories and practices in order to make informed decisions and achieve financial success. The study continues by underlining the importance of continuous financial planning and adaption in order to support long-term corporate growth.